2021
DOI: 10.3389/fpls.2021.719587
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Pentyl Leaf Volatiles and Their Role in Resistance to Anthracnose Leaf Blight

Abstract: Volatiles are important airborne chemical messengers that facilitate plant adaptation to a variety of environmental challenges. Lipoxygenases (LOXs) produce a bouquet of non-volatile and volatile oxylipins, including C6 green leaf volatiles (GLVs), which are involved in a litany of plant physiological processes. GLVs are emitted by a diverse array of plant species, and are the best-known group of LOX-derived volatiles. Five-carbon pentyl leaf volatiles (PLVs) represent another widely emitted group of LOX-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Previous reports showed that exogenous treatment with several of these α‐ and γ‐ketols increased resistance against C. graminicola in maize (Wang et al, 2020a , 2020b ). Moreover, increased resistance to ALB by treatment with pentyl leaf volatiles was associated with increased levels of these defensive ketols (Gorman et al, 2021 ). Therefore, both increased JA and reduced levels of defensive ketols in the opr2 mutant may explain at least in part its increased susceptibility to this pathogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that exogenous treatment with several of these α‐ and γ‐ketols increased resistance against C. graminicola in maize (Wang et al, 2020a , 2020b ). Moreover, increased resistance to ALB by treatment with pentyl leaf volatiles was associated with increased levels of these defensive ketols (Gorman et al, 2021 ). Therefore, both increased JA and reduced levels of defensive ketols in the opr2 mutant may explain at least in part its increased susceptibility to this pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…GLV measurement was performed following the methods described in He et al ( 2020 ) and Gorman et al ( 2021 ). In brief, leaves of the opr2‐1 mutant and its WT were infected with C. graminicola for 7 days and excised for imaging, with a delay of approximately 40 min between scanning and volatile collection.…”
Section: Methodsmentioning
confidence: 99%
“…6-methyl-heptadiene-2-one, 6-methyl-5-hepten-2-ol, and 6-methyl-5-heptene-2-one were structurally similar. In the LOX pathway, 1-penten-3-ol is dehydrogenated to produce 1-penten-3-one [ 47 ]. Similarly, 6-methyl-5-heptene-2-one might be altered in a single step to produce 6-methyl-3,5-heptadiene-2-one and 6-methyl-5-hepten-2-ol ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these studies indicated that both 9-and 13-ketols serve as important signals for the induction of ISR in maize [22,42]. Additionally, several ketols, including 9,10-KODA, 9,12-KODA, 13,12-KODA, and 13,12-KOMA, were upregulated in Colletotrichum graminicola-infected maize plants that were treated with pentyl leaf volatiles (PLVs); suggesting a positive correlation with PLV-mediated pathogen resistance [43]. The 9,10-KODA and other 9-LOX products were highly induced upon infection of maize stems by the hemibiotrophic pathogen Fusarium graminearum Petch, the causal agent of Gibberella Stalk Rot (GSR) [44].…”
Section: Ketols Serve Signaling Roles In Plant-pathogen Interactionsmentioning
confidence: 91%